2019
DOI: 10.3390/cancers11030350
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Trioxide and (−)-Gossypol Synergistically Target Glioma Stem-Like Cells via Inhibition of Hedgehog and Notch Signaling

Abstract: Glioblastoma is one of the deadliest malignancies and is virtually incurable. Accumulating evidence indicates that a small population of cells with a stem-like phenotype is the major culprit of tumor recurrence. Enhanced DNA repair capacity and expression of stemness marker genes are the main characteristics of these cells. Elimination of this population might delay or prevent tumor recurrence following radiochemotherapy. The aim of this study was to analyze whether interference with the Hedgehog signaling (Hh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(113 citation statements)
references
References 78 publications
10
102
0
1
Order By: Relevance
“…Arsenic trioxide was shown to induce ACD and cell death in various tumor cell populations in multiple studies, including our own [14,[56][57][58]. Considering that arsenic trioxide is already clinically used to treat acute promyelocytic leukemia (APL) [59] and easily crosses the blood-brain-barrier [60], this drug could be particularly interesting for hard-to-treat cancers, such as brain tumors (primary or metastases).…”
Section: Pro-death Autophagymentioning
confidence: 95%
See 1 more Smart Citation
“…Arsenic trioxide was shown to induce ACD and cell death in various tumor cell populations in multiple studies, including our own [14,[56][57][58]. Considering that arsenic trioxide is already clinically used to treat acute promyelocytic leukemia (APL) [59] and easily crosses the blood-brain-barrier [60], this drug could be particularly interesting for hard-to-treat cancers, such as brain tumors (primary or metastases).…”
Section: Pro-death Autophagymentioning
confidence: 95%
“…Interestingly, we could also recently show that the combination of arsenic trioxide and AT-101 caused a strong upregulation of HMOX1 in glioma stem-like cells (GSCs) [56], indicating that more specialized cell populations can also be targeted with drugs employing these pathways. In summary, we recently provided novel evidence that the decrease in mitochondrial mass and function induced by AT-101 is due to robust over activation of mitophagy that finally culminates in the demise of the cancer cells.…”
Section: Pro-death Mitophagy Triggered By Gossypol/at-101mentioning
confidence: 99%
“…On the other hand, As 2 O 3 decreased the population of stem cell-like cancer cells (CSLC) in U87-MG, U251-MG, and U373MG glioma cell lines by blocking the Notch signaling pathway, decreasing the concentration of Nocht1 and Hes1 [251]. In addition, Linder et al reported that a combination of As 2 O 3 plus AT101 (a BH3-mimetics, inhibitor of the pro-apoptotic proteins Bcl-2, Bcl-xL, and Mcl-1) showed a synergistic effect against CSLC by inhibiting the Hedgehog and Notch signaling pathways [252]. In a neurosphere model of glioblastoma, a decrease in growth and proliferation was observed, as well as an increase in caspase-3 levels after treating with As 2 O 3 the HSR-GBM1, 040622 (TMZ-resistant) and 040821 (TMZ-sensitive) cell lines.…”
Section: ∆9-tetrahydrocannabinol (Thc) and Cannabinol (Cbd) (Cannabinmentioning
confidence: 99%
“…• Increases caspase 3, inhibits PTCH1b, N-Myc, and GLI2 (transcriptional targets of Hg pathway), and inhibits HES5 and HEY1 (transcriptional targets of Notch pathway) [252].…”
Section: Everolimusmentioning
confidence: 99%
“…The original articles in this special issue present novel findings on molecular mechanisms of radiosensitization, radioresistance and acquired resistance to therapy (Kessler et al, Müller-Längle et al, Shah et al, Llaguno-Munive et al) [1,2,3,4], cell migration (Nowicki et al, Hübner et al) [5,6], intracellular drug levels (Colin et al) [7], strategies targeting renewal capacities of cancer stem-like cells (Gravina et al, Sansalone et al, Linder et al) [8,9,10], mathematic modeling of synergy, machine learning, deep learning (Kim et al, Hana et al, Wong et al) [11,12,13], distinct signaling pathways (Barbagallo et al, Akgül et al, Bensalma et al, Saito et al, Liu et al) [14,15,16,17,18], prognostic and predictive effects of imaging patterns (Jungk et al, Puig et al) [19,20], tumor-associated epilepsy (Berendsen et al) [21], and novel models and experimental therapeutic approaches (Berthier et al, Offenhäuser et al, Privat-Maldonado et al, Lozada-Delgado et al) [22,23,24,25].…”
mentioning
confidence: 99%